Informing the Government of Flanders' investment in agricultural advisory services to Malawian farmers - CGIAR Research Program on Policies, Institutions, and Markets (2018)
The Government of Flanders used PIM research on advisory services to farmers in Malawi for putting together their country strategy document for Malawi. Agricultural advisory services is one of four priority areas highlighted in this document and will benefit from an investment of 6 million euros from the Government of Flanders in 2019-2023.